Comparison Between The Flipped Classroom Learning Model and Contextual Teaching and Learning in Improving Students Speaking Skills - Nadiahanayati Nadiahanyati; Suryadi Suryadi (UNDIKMA, 2023)
The aims of this research is to help students become more confident public speakers. The research approach is an experiment using a posttest-only control group design. Thirty undergraduates served as the study's sample, which was split evenly between two groups. Using a t-test with a significance threshold of = 0.05, the researchers calculated (n1+ n2-2) = 28 and got a result of 1.701, while the tcount value from the test was 2.355. If tcount > ttable, then Ho is ruled out. It follows that the group using the contextual teaching and learning model had a greater impact (= 73.00 and s = 8.194) than the group using the traditional approach (= 76.67 and s = 9.194) on students' gains in fluency in speech. The study's findings suggest that, in comparison to the flipped classroom approach, the contextual teaching and learning model is more effective at fostering students' growth in their oral communication skills.